Burrow architecture and digging activity in the Cape dune mole rat - Thomas, H.; Bateman, Bill; Le Comber, S.; Bennett, N.; Elwood, R.; Scantlebury, M. (Wiley-Blackwell Publishing Ltd., 2009)
While females are traditionally thought to invest more time and energy into parentalcare than males, males often invest more resources into searching and displaying formates, obtaining mates and in male–male conflict. Solitary subterranean mammalsperform these activities in a particularly challenging niche, necessitating energeticallyexpensive burrowing to both search for mates and forage for food. This restrictionpresumably affects males more than females as the former are thought to dig longertunnels that cover greater distances to search for females. We excavated burrowsystems of male and female Cape dune mole rats Bathyergus suillus the, largest trulysubterranean mammal, to investigate whether male burrows differ from those offemales in ways that reflectmate searching bymales. We consider burrow architecture(length, internal dimensions, fractal dimension of tunnel systems, number of nestingchambers and mole mounds on the surface) in relation to mating strategy. Malesexcavated significantly longer burrow systems with higher fractal dimensions andlarger burrow areas than females.Male burrow systems were also significantly fartherfrom one another than females were from other females’ burrow systems. However,no sex differences were evident in tunnel cross-sectional area, mass of soil excavatedper mound, number of mounds produced per unit burrow length or mass of soilexcavated per burrow system. Hence, while males may use their habitat differentlyfrom females, they do not appear to differ in the dimensions of the tunnels they create.Thus, exploration and use of the habitat differs between the sexes, which may be aconsequence of sex differences in mating behaviour and greater demands for food.